Indução ao florescimento precoce de genótipos de tabaco pela aplicação de hormônio e cultivo em vasos pequenos - Scheffel, Lúcio Gabriel (2021)
The use of late flowering tobacco lines becomes essential in breeding programs due to their morphological traits. These strains present a long vegetative period when cultivated at a given time, making it difficult to collect pollen and crosses. The objectives of this work were: to induce the early flowering of tobacco genotypes by the application of gibberellic acid (GA3) and by cultivation in root-restricted pots and to analyze the economic viability in anticipating the flowering of tobacco genotypes. The completely randomized design was used, with five replications, composed of a factorial with five genotypes (K326, KM10, LF, TN90 and BU459) and four concentrations of gibberellic acid (0, 50, 100 and 200 mgL-¹ of GA3) and five additional treatments (genotypes in smaller pots). The data were submitted to an analysis of individual variance and for the traits number of flowers in the 5th; 10th; 20th; 30th day; sum of flowers; and seed mass regression analysis was performed, and the genotype x GA3 concentration interaction was significant. For the additional ones, a means test was performed. The factorial treatments showed early floral induction for the highest GA3 concentration in both seasons as well as the additional treatments, except for LF genotypes (exp. I) and TN90 (exp. II). The sum of flowers and grain mass showed a suppression with the highest GA3 concentrations and in the additional treatments. A savings of 14.5% was obtained by inducing early flowering of tobacco genotypes.